The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1109/tpwrs.2017.2745410
|View full text |Cite
|
Sign up to set email alerts
|

Chance-Constrained AC Optimal Power Flow: Reformulations and Efficient Algorithms

Abstract: Higher levels of renewable electricity generation increase uncertainty in power system operation. To ensure secure system operation, new tools that account for this uncertainty are required. In this paper, we adopt a chance-constrained AC optimal power flow formulation, which guarantees that generation, power flows and voltages remain within their bounds with a pre-defined probability. We then discuss different chanceconstraint reformulations and solution approaches for the problem. We first describe an analyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
185
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(198 citation statements)
references
References 40 publications
0
185
0
Order By: Relevance
“…Previous studies, e.g., [13], [17], [21], have shown that this approximation limits the joint violation probability effectively due to a few simultaneously active constraints. Further treatment of (2) depends on the assumption made on uncertainty ω.…”
Section: Stochastic Market Via Chance Constraintsmentioning
confidence: 99%
“…Previous studies, e.g., [13], [17], [21], have shown that this approximation limits the joint violation probability effectively due to a few simultaneously active constraints. Further treatment of (2) depends on the assumption made on uncertainty ω.…”
Section: Stochastic Market Via Chance Constraintsmentioning
confidence: 99%
“…In order to consider the impact of generation uncertainty, we follow our previous work [23], [33] and we re-formulate the problem using chance constraints [34], [35]. We assume that the PV power injection is the only source of uncertainty (load uncertainty can be also included in a similar way) and we use as input forecast error distributions with different forecasting horizons (1 to 24 hours ahead).…”
Section: A Accounting For Uncertainty Through Chance Constraintsmentioning
confidence: 99%
“…E.g., the voltage and current magnitude constraints are reformulated as P {V min ≤ |V j,t | ≤ V max } ≥ 1 − ε and P |I br i,t | ≤ I i max ≥ 1 − ε, respectively. To solve the resulting CC-OPF, we interpret the probabilistic constraints as tightened deterministic versions of the original constraints following the work of [34], [35]. The tightening represents a security margin against uncertainty, i.e., an uncertainty margin.…”
Section: A Accounting For Uncertainty Through Chance Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here in (3) explicit expression for G w , as a function ofx c ,x u , α, is skipped due to space limitations; the objective function is split in two parts, correspondent to mean and fluctuations, respectively. Following the approach of [8]- [10], we are able to evaluate the expectation and the probabilities in (3) analytically. Moreover, the analytic evaluation returns explicit dependencies onx c and α, therefore stating the Cloud-AC-OPF (3) as the following tractable deterministic optimization formulation:…”
Section: E Cloud-ac-opf: Analytic Reformulationmentioning
confidence: 99%